2019
DOI: 10.1111/cyt.12755
|View full text |Cite
|
Sign up to set email alerts
|

A 2‐year retrospective study on pleural effusions: A cancer centre experience

Abstract: Background Cytopathological examination of pleural effusions is a fast and minimally invasive method for verification of the presence of neoplastic cells. We report our 2‐year experience using a categorised diagnostic system and reporting risks of malignancy (ROMs) for each defined category. Methods Cytological reports of patients between November 2016 and October 2018 were collected, with results primarily classified into a five‐tiered classification scheme. Immunohistochemistry markers used in cytology and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
14
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
10
14
1
Order By: Relevance
“…Pericardial effusions only included three cases, and their distribution was 33.33% (one case) NFM and 66.67% (two cases) MAL. Our results are compatible with those of other studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], some of which include only pleural effusions [ 25 , 26 , 27 , 30 ], while others include pleural and peritoneal effusions [ 24 , 28 , 31 , 32 ], and one includes only pericardial effusions [ 29 ]. In regard to pleural effusions, the rate of malignancy reported from oncologic centers is significantly higher [ 31 ], while a similar rate to ours is reported from other institutions [ 26 ], probably related to the “general” nature of our institution.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pericardial effusions only included three cases, and their distribution was 33.33% (one case) NFM and 66.67% (two cases) MAL. Our results are compatible with those of other studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], some of which include only pleural effusions [ 25 , 26 , 27 , 30 ], while others include pleural and peritoneal effusions [ 24 , 28 , 31 , 32 ], and one includes only pericardial effusions [ 29 ]. In regard to pleural effusions, the rate of malignancy reported from oncologic centers is significantly higher [ 31 ], while a similar rate to ours is reported from other institutions [ 26 ], probably related to the “general” nature of our institution.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, for peritoneal effusions, the corresponding values were 80%, 99.3%, 98.5% and 89.6%. The accuracy parameter values are in line with those reported in other studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Notably, oncologic centers report lower sensitivity [ 25 , 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…A meta‐analysis of 73 studies reported a mean ROM for the AUS and SFM categories of 65.9% and 81.8%, respectively 19 . Another recently published single‐institution study reported an ROM of 50% and 83.3% for AUS and SFM cases, respectively 20 . By comparison, the ROM for both the AUS and SFM categories in our study was lower (39% and 64%, respectively) than that in the published data.…”
Section: Discussioncontrasting
confidence: 74%
“…In this same year, Valerio et al reported on a series of 65 pleural effusions with matching biopsies and found a ROM of 50% for ND, 44% for NFM, 50% for AUS, 83.3% for SFM, and 96.2% for MAL. They reported a sensitivity of 69.4%, a specificity of 93.3%, a PPV of 96.2%, and an NPV of 56% [ 24 ].…”
Section: Discussionmentioning
confidence: 99%